PENERAPAN KAIDAH ADH-DHARARU YUZALU DALAM PENENTUAN NASAB BAYI TERTUKAR MENGGUNAKAN TES DNA: STUDI HUKUM ISLAM KONTEMPORER - Wirna; Hendri Sayuti (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study discusses the application of the fiqh principle of al-dhararu yuzalu in determining the lineage of switched babies by utilizing DNA testing technology as a means of proof. The issue of switched babies in hospitals poses a major dilemma in terms of identity, human rights, and Sharia law, as it has the potential to cause errors in lineage that affect inheritance rights, the validity of marriage guardians, and mahram status. This study uses a literature-based qualitative method, examining the limitations of traditional methods of determining lineage (al-firasy, al-iqrar, al-bayyinah, and al-qiyafah) and the caution of Islamic law in accepting new technology. The results of the study show that some religious authorities, such as NU and Darul Ifta Egypt, agree that DNA testing can be used as an aid in determining lineage, but not as the sole legal basis. The application of the principle of al-dhararu yuzalu that harm must be eliminated becomes an integrative basis for addressing this issue fairly and in accordance with the objectives of Sharia law, in order to prevent greater social, psychological, and Sharia harm resulting from errors in lineage identification.